2001
DOI: 10.1159/000050508
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lung Natural Killer Cell Activity by Smoking: The Role of Alveolar Macrophages

Abstract: Background: It is known that natural killer (NK) cell activity in the lung of smokers (SM) is lower than in non-smokers (NS). However, little is known about the underlying mechanisms. Objective: The purpose of this work was to investigate the mechanisms of the inhibition of NK cell activity by alveolar macrophages (AM) in SM. Methods: Lung effector cells and AM were obtained using bronchoalveolar lavage. The NK cell activity was assayed by 51Cr release method after incubation of 4 and 24 h, using K5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…These findings suggest that the inhibition of AM-mediated LPS-induced B lymphocyte proliferation in CS-exposed mice is probably caused by excessive increased superoxide and hydrogen peroxide generations by cigarette smoking. We have previously reported that the AM-mediated inhibition of natural killer cell activity in cigarette smokers was prevented by SOD [8]. Therefore, excessive increased superoxide and hydrogen peroxide generations in AM from CS-exposed mice may lead to oxidant stress for pulmonary immune system and inhibit immune functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the inhibition of AM-mediated LPS-induced B lymphocyte proliferation in CS-exposed mice is probably caused by excessive increased superoxide and hydrogen peroxide generations by cigarette smoking. We have previously reported that the AM-mediated inhibition of natural killer cell activity in cigarette smokers was prevented by SOD [8]. Therefore, excessive increased superoxide and hydrogen peroxide generations in AM from CS-exposed mice may lead to oxidant stress for pulmonary immune system and inhibit immune functions.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that AM in cigarette smokers exerted significantly greater suppressive effect on autologous natural killer cell activity than AM in nonsmokers because of increased oxygen radical by CS [8]. In this study, we investigated whether there was a difference between CS-exposed and non-CS-exposed mice in the response of AM on lipopolysaccharide (LPS)-induced B lymphocyte proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, smoking contributes to an increase in the white blood cell count and a decline in the circulating natural killer (NK) cell count [13]. Third, smoking has been reported to reduce local airway immunity and that the alveolar macrophages of smokers suppressed NK cell activity by producing prostaglandins and oxygen radicals [14]. Taken together, smoking not only causes lung cancer but it also might negatively affect the prognosis of patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…6). It has previously been reported that CS increased reactive oxygen species (ROS) generation in AM [11], [12]. CS-induced DNA damage may cause by excess of ROS production.…”
Section: Effect Of Cs On Dna Damage In Ammentioning
confidence: 99%